PENERAPAN MODEL STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) DENGAN MEDIA GAZEBO PUZZLE CONSTRUCTION UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN MENGGAMBAR SAMBUNGAN KAYU BAGI SISWA KELAS X TEKNIK GAMBAR BANGUNAN SMK N 2 WONOSOBO SEMESTER GENAP TAHUN 2015/2016 - Amin Nurita Fajar Astuti (Universitas PGRI Semarang, 2016)
This research was focused on how the process and the motivation improvement and the skills of Class X TGB1 students at SMK N 2 Wonosobo in drawing various kinds of wood connection after implementing Student Teams Achievement Division (STAD) Model with Puzzle Gazebo Construction Media.There were two cycles used in this research, each of which contains planning, action, observing and reflecting. The Subjects of the research were the motivation and the skills of Class X TGB1 students at SMK N 2 Wonosobo in drawing various kinds of wood connection. Based on the result of the research, it was known that there was an increasing on the motivation and the skills of Class X TGB1 students at SMK N 2 Wonosobo in drawing various kinds of wood connection. The result showed that the motivation got Good category on Pre-cycle for 7 students (24.14%), Cycle 1 for 18 students (62.09%) and Cycle 2 for 24 students (82.76%) from 29 students at whole, Whereas, the skill of drawing various kinds of wood connection got average score 68.6 on Pre-cycle; 73.3 on Cycle I and 77.6 on Cycle II, with the percentage of score > 76.0, on Pre-cycle, it was 3.45%, Cycle I was 37.93% and Cycle II was 75.86%. Keywords: STAD Model, Learning Motivation, Drawing Skill for Wood Connection